Insight into Unprecedented Diversity of Cyanopeptides in Eutrophic Ponds Using an MS/MS Networking Approach - Kust, Andreja; Řeháková, Klára; Vrba, Jaroslav; Maicher, Vincent; Mareš, Jan; Hrouzek, Pavel; Chiriac, Maria-Cecilia; Benedová, Zdeňka; Tesařová, Blanka; Saurav, Kumar (Toxins, 2020)
Man-made shallow fishponds in the Czech Republic have been facing high eutrophication since the 1950s. Anthropogenic eutrophication and feeding of fish have strongly affected the physicochemical properties of water and its aquatic community composition, leading to harmful algal bloom formation. In our current study, we characterized the phytoplankton community across three eutrophic ponds to assess the phytoplankton dynamics during the vegetation season. We microscopically identified and quantified 29 cyanobacterial taxa comprising non-toxigenic and toxigenic species. Further, a detailed cyanopeptides (CNPs) profiling was performed using molecular networking analysis of liquid chromatography-tandem mass spectrometry (LC-MS/MS) data coupled with a dereplication strategy. This MS networking approach, coupled with dereplication, on the online global natural product social networking (GNPS) web platform led us to putatively identify forty CNPs: fourteen anabaenopeptins, ten microcystins, five cyanopeptolins, six microginins, two cyanobactins, a dipeptide radiosumin, a cyclooctapeptide planktocyclin, and epidolastatin 12. We applied the binary logistic regression to estimate the CNPs producers by correlating the GNPS data with the species abundance. The usage of the GNPS web platform proved a valuable approach for the rapid and simultaneous detection of a large number of peptides and rapid risk assessments for harmful blooms.
Keywords: rybníky; Chromatography, High Pressure Liquid; Tandem Mass Spectrometry; Population Dynamics; Metabolomics; Harmful Algal Bloom; mikrobiota; Environmental Monitoring; cyanobacteria; Water Microbiology; metabolomika; Microbiota; mořské toxiny; Marine Toxins; online sociální sítě; cyanopeptides; populační dynamika; sinice; hmotnostní spektrometrie s elektrosprejovou ionizací; tandemová hmotnostní spektrometrie; liquid chromatography-tandem mass spectrometry; monitorování životního prostředí; roční období; Ponds; global natural product social networking (GNPS); Bacterial Toxins; Seasons; harmful bloom; Czech Republic; Online Social Networking; mikrobiologie vody; Spectrometry, Mass, Electrospray Ionization; Risk Assessment; dereplication strategy; bakteriální toxiny; Česká republika; škodlivý vodní květ; Cyanobacteria; hodnocení rizik; vysokoúčinná kapalinová chromatografie